Reindeer breathe less and save water in the cold - Nilssen, Kjell J.; Rognmo, Arne; Blix, Arnoldus Schytte (Rangifer, 1990)
Simultaneous measurements of metabolic rate, respiratory minute volume, respiratory frequency, and oxygen extraction from the inspired air were obtained during treadmill exercise in Svalbard reindeer (Rangifer tarandus platyrhynchus) and Norwegian reindeer (Rangifer tarandus tarandus). The experiments were carried out both in summer and winter at ambient temperatures and running speeds ranging from +12 to -30 °C and 3.7 to 9.0 knvh1, respectively. We found that respiratory minute volume was generally lower in summer than in winter for a similar ambient temperature, and also that respiratory minute volume was reduced at low ambient temperature both in summer and winter. The change in respiratory minute volume was inversely related to oxygen extraction, the latter being at its highest at the lowest ambient temperature and running speed in summer. Reduction of respiratory minute volume, and hence respiratory water loss, at low ambient temperature is likely to contribute significantly to the survival of these species, particularly in winter when the animals can only replace body water with snow at low temperature.